A rationale for the influence of grain size on failure of magnesium alloy AZ31: An in situ X-ray microtomography study. (November 2020) - Azghandi, S.H. Mohamadi; Weiss, M.; Arhatari, B.D.; Adrien, J.; Maire, E.; Barnett, M.R.
Abstract: The present study employs in situ X-ray microtomography to characterize the impact of grain size on void nucleation, growth and linkage during tensile loading of magnesium alloy AZ31. It was found that the tensile strain to failure increased almost threefold when the grain size was reduced from 60 to 3 μm. Grain refinement led to reduced twin formation and reduced void growth rates but did not impact markedly on the relationship between strain and the detected void number density. Because the finer grained samples experienced higher strains to failure, greater void number densities were thus detected at failure in these samples. The void volume fraction at failure remained constant despite changing grain size, within error. Final failure occurs via a shear localization and there appears to be a role of void formation in triggering the final shear instability. We thus favour ascribing failure to a void-sheeting type mechanism. Failure is seen to follow rapidly after a critical void volume fraction is attained and this is broadly consistent with predictions made via the application of a simple McClintock model. The higher strains to failure in the present fine-grained samples are thus ascribed chiefly to the lower rates of void growth. The suppression of void growth by grain refinement seen here may explain why finer grain magnesium alloys often display higher tensile ductility. Graphical abstract: Image, graphical abstract